1965
DOI: 10.1128/jb.89.3.597-602.1965
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Enhancement of Infectivity of Reovirus

Abstract: enhancement of infectivity of reovirus. J. Bacteriol. 89:597-602. 1965.-Enhancement of infectivity by chymotrypsin treatment has been demonstrated with all three types of reovirus, although not in all viral preparations. Enzyme treatment did not produce a simultaneous increase in the hemagglutinating activity of reovirus type 1 (the only type tested). The infectivity of reovirus type 1 (Lang strain) was increased by treatment with chymotrypsin, trypsin, papain, and a filtrate from a culture of a Pseudomonas sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

1968
1968
1996
1996

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…The protective effect of lacteal TIs may thus be of shorter duration. It is tempting to speculate whether the TIs we have described, which seem to show antirotaviral activity, may also act against other viruses which show enhanced cell culture growth in the presence of trypsin, such as reovirus (25,29) and influenza A viruses (14). Possibly, the nonlipid, nonantibody, noninterferon macromolecule recently detected in human milk (17), which seems to inhibit a range of viruses including rotavirus (27), could also be a TI.…”
Section: Resultsmentioning
confidence: 95%
“…The protective effect of lacteal TIs may thus be of shorter duration. It is tempting to speculate whether the TIs we have described, which seem to show antirotaviral activity, may also act against other viruses which show enhanced cell culture growth in the presence of trypsin, such as reovirus (25,29) and influenza A viruses (14). Possibly, the nonlipid, nonantibody, noninterferon macromolecule recently detected in human milk (17), which seems to inhibit a range of viruses including rotavirus (27), could also be a TI.…”
Section: Resultsmentioning
confidence: 95%
“…Enhanced plaque formation by proteolytic enzymes has been reported for reoviruses by chymotrypsin, trypsin and papain [15,16], and pancreatin [4,19], vaccinia virus by trypsin and chymotrypsin [7,8], enteroviruses by pancreatin [20], influenza A and B viruses by pancreatin and trypsin [1], and parainfluenza virus type 3 [13] and type 4 [10] by trypsin. Spendlove and Schaffer [16] suggested that the enhanced plaque formation of reoviruses by proteolytic enzymes resulted from the action of the enzyme on a virus-associated substrate. Lerner et al [9], however, reported that trypsin treatment of reovirus type 2 or Coxsackie B5 had little or no effect on infectivity, but similar treatment of reovirus type 1 increased infectivity titers.…”
Section: Discussionmentioning
confidence: 96%
“…Enzyme treatment and virus assay. Enhancement of the infectivity of reovirus preparations treated with proteolytic enzymes was done by the method of Spendlove and Schaffer (26), except that virus preparations were exposed to 200 p.g of trypsin per ml of sample. Assays of IV and PIV were performed before and after the trypsin treatment on Maden-Darby bovine kidney cells.…”
Section: Methodsmentioning
confidence: 99%